31. Sensory peripheral neuropathy in a novel mutation of FLVCR1. Issue 4 (April 2016) - Pro, S.; De Luca, M.; Miliucci, R.; Alessandri, B.; Di Capua, M.
Abstract : Posterior Column Ataxia and Retinitis Pigmentosa (PCARP) is an autosomal-recessive neurodegenerative syndrome. Standard phenotype expected: areflexia and retinitis pigmentosa in infancy; night blindness and peripheral visual field loss in late childhood; evaluation to sensory ataxia secondary to degeneration of the posterior columns of the spinal cord. We reported a case of 3 yrs old children with PCARP secondary to FLVCR1 mutation and atypical phenotype. Our patient have a congenital and progressive acro-osteolysis of fingers and precocious ataxia with general hypotonia, and deep tendon reflex absent in the legs. No visual impairment was reported and the fundus oculi was normal. ERG was normal. Nerve conduction study showed sensory peripheral neuropathy. Median-nerve SEPs were not recordable for sensitive neuropathy. Brain and total spinal cord MRI was normal. Genetic study showed a truncated FLVCR1 protein by mother and new potentially pathogenetic mutation by father. Sensory peripheral neuropathy was reported in only few cases of PCARP.